Collagen Sponge Functionalized with Chimeric Anti-BMP-2 Monoclonal Antibody Mediates Repair of Critical-Size Mandibular Continuity Defects in a Nonhuman Primate Model. (16th March 2017) - Xie, Yilin; Su, Yingying; Min, Seiko; Tang, Jianxia; Goh, Bee Tin; Saigo, Leonardo; Ansari, Sahar; Moshaverinia, Alireza; Zhang, Chunmei; Wang, Jinsong; Liu, Yi; Khojasteh, Arash; et al.
Abstract : Antibody-mediated osseous regeneration (AMOR) has been introduced by our research group as a tissue engineering approach to capture of endogenous growth factors through the application of specific monoclonal antibodies (mAbs) immobilized on a scaffold. Specifically, anti-Bone Morphogenetic Protein- (BMP-) 2 mAbs have been demonstrated to be efficacious in mediating bone repair in a number of bone defects. The present study sought to investigate the application of AMOR for repair of mandibular continuity defect in nonhuman primates. Critical-sized mandibular continuity defects were created in Macaca fascicularis locally implanted with absorbable collagen sponges (ACS) functionalized with chimeric anti-BMP-2 mAb or isotype control mAb. 2D and 3D analysis of cone beam computed tomography (CBCT) imaging demonstrated increased bone density and volume observed within mandibular continuity defects implanted with collagen scaffolds functionalized with anti-BMP-2 mAb, compared with isotype-matched control mAb. Both CBCT imaging and histologic examination demonstrated de novo bone formation that was in direct apposition to the margins of the resected bone. It is hypothesized that bone injury may be necessary for AMOR. This is evidenced by de novo bone formation adjacent to resected bone margins, which may be the source of endogenous BMPs captured by anti-BMP-2 mAb, in turn mediating bone repair.